Marketing the unknown developing market strategies for technical innovations - Millier, Paul (John Wiley & Sons, 1999)
In this book, Paul Millier demonstrates that products have a 'life' before their 'life cycle'. He has developed the techniques of a marketing strategy which can be applied to products which do not yet exist on the market place and for markets which themselves do not exist - in essence a marketing strategy for technical innovations. This practical book will pave the way for marketing managers, R&D managers and project managers in industrial organizations to successfully launch and market innovations in a very competitive field and will enable the reader to outline strategies for further development.